A Rare Case of a Synchronous Anaplastic Carcinoma Thyroid with Ductal Carcinoma Breast - Saptarshi Ghosh; P. B. Ananda Rao; Shreyasee Sarkar; Sivasankar Kotne; S. P. V. Turlapati; Anindita Mishra (Case Reports in Oncological Medicine)
Dual malignancy was first reported by Billroth in 1889. Incidence of second malignancy in cancer patients is as high as 10%, but synchronous anaplastic thyroid cancer along with breast tumor is a rare entity. We present a case of a 61-year-old female with a synchronous anaplastic carcinoma thyroid with ductal carcinoma breast. The plausible association of breast cancers with thyroid carcinomas should thus be evaluated in larger cohort studies. More importantly, this report is to highlight the unusual synchronous occurrence of anaplastic thyroid cancer with ductal breast cancer and the therapeutic challenges involved in such cases.